Gambaran Pengetahuan dan Sikap Orang Tua Tentang Makanan Kariogenik pada Anak Usia Prasekolah Yang Menyebabkan Karies Gigi di Tk ‘Aisyiyah Karangasem - Fitri Shinta Muliya; Fida’ Husain (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The problem of dental caries in early childhood is important because dental caries is an success indicator of efforts to maintain children's dental health. The incidence of caries in children is influenced by the knowledge and attitudes of parents in caring for dental health. According to the Central Java region, there were 43.45% of data on damaged, perforated, and sick teeth, and for the Surakarta area there were 35.66%). This study aims to describe the knowledge and attitudes of parents about cariogenic foods consumed by preschoolers that can cause dental caries. This type of research is descriptive with quantitative methods. The sampling technique used is total sampling with the sampling technique based on the criteria determined by the researcher. the description of the mother's knowledge about cariogenic foods that can cause dental caries is mostly good with 83 respondents (57.60%) and the mother's attitude is mostly good, which is 80 respondents (55.60%). Knowledge and attitude of parents about cariogenic food in preschoolage that causes dental caries are good in TK 'Aisyiyah Karangasem.